Clinical factors affecting the rate of exodrift after surgery in patients with basic intermittent exotropia - Seungheon Kim (Nature Portfolio, 2021)
Abstract We investigated the period of postoperative exodrift during follow-up and clinical factors that affect the rate of exodrift after surgery in the patients with intermittent exotropia (IXT). A retrospective review of medical records of patients with exodrift who underwent bilateral rectus recession for IXT was performed. Exodrift was defined as angle of deviation greater than 10 prism diopters (PD) at distance and near. The median survival period of postoperative exodrift was analyzed using Kaplan Meier survival analysis. The patients were divided into two groups according to the median period of postoperative exodrift (early and late group). The weighted Cox’s proportional hazards regression analysis to investigate the risk factors that affect rate of postoperative exodrift was performed. A total of 108 patients was included. The preoperative angle of deviation at distance and near were 30.3 ± 7.2 PD and 29.5 ± 8.6 PD, respectively. The median survival period of postoperative exodrift was 24 months (range, 6–48 months).The angle of deviation at postoperative day 1 in early and late group were − 3.8 ± 5.5 PD (range, − 16–8 PD) and − 7.7 ± 4.6 PD (range, − 16–4 PD) (p < 0.01). Minus value means esodeviation. In regression analysis, the angle of deviation at postoperative day 1 was the significantly related with rate of exodrift (p < 0.01). The median period of exodrift after surgery was 24 months, angle of deviation at postoperative day 1 could affect the rate of exodrift in patients with IXT.